Sulphate Pulping of Giant Bamboo (Dendrocalamus Giganteus) - Guha, S. R. D.; Dhoundiyal, S. N.; Mathur, G. M. (Indian Forester, 1975)
Bamboo is the main source of fibrous raw material for pulp and paper industry. Various species of bamboo are being used for this purpose. The main species used is Dendrocalamus strictus. The Forest Botanist, Forest Research Institute suggested that Dendrocalamus giganteus (I) which is the largest of bamboos should also be tested as this species of bamboo has not so far been used for the production of paper. The results of a comparative laboratory scale investigation or Dendrocalamus giganteus and D. strictus are recorded in this paper.